Comparison of wheatgrass (A. intermedium) and tall wheatgrass (A. elongatum) in transpiration viewpoint - Rahimzadeh Halagh, N.; Sadeghi, S.H.R. (Caspian Journal of Environmental Sciences, 2007)
Transpiration, as one of the components of hydrological cycle, has not been paid enough attention yet, while it is necessary for sound utilization of rangelands, mostly located in the arid and semiarid regions. The comparison of the different kinds of rangelands species in terms of transpiration rates provides range managers the required information to achieve optimal forage production for a given input precipitation. The present study is a preliminary comparison in transpiration between two important Iranian rangeland species viz. A. intermedium and A. elongatum. The amounts of daily evapotranspiration from aforesaid species of which 4?5 shoots were initially planted in small polyethylene pots with surface area of 50.27 cm2 in five replicates were measured using weighing technique for a period of 33 days under relatively natural conditions. The amounts of daily transpiration of A. intermedium and A. elongatum were respectively varied from 1.4 to 9.4 and 1.5 to 9.1 milliliter. The results of the statistical analyses showed that there is no a significant difference between the amounts of transpiration for the two species on dry matter basis and therefore, the species may have the same value in rangeland improvement from transpiration point of view.